2010
DOI: 10.1590/s0365-05962010000600006
|View full text |Cite
|
Sign up to set email alerts
|

Comparação entre a concentração de mastócitos em carcinomas espinocelulares da pele e da cavidade oral

Abstract: FUNDAMENTS:The lethality of squamous cell carcinomas (SCC) of the skin is considered low. SCC in the mouth is usually associated with poor prognosis. Current evidence suggests that mast cells in the normal tissue contribute to the tumorigenesis of SCC, probably by promoting angiogenesis. OBJECTIVE: The aim of this study was to compare the concentration of mast cells in SCC of the mouth and skin and evaluate whether there is a correlation with the degree of differentiation of these tumors. MATERIAL AND METHODS:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 15 publications
0
7
0
4
Order By: Relevance
“…FLAVIO MACIEL DE FREITAS NETO 1 LEONARDO MILANESI POSSAMAI 1 CAROLINE BATTISTI 1 ELISETE PEREIRA DE SOUZA 1,2 PEDRO BINS ELY 1,2 35ª Jornada Sul Brasileira de Cirurgia Plástica…”
Section: Objetivounclassified
See 1 more Smart Citation
“…FLAVIO MACIEL DE FREITAS NETO 1 LEONARDO MILANESI POSSAMAI 1 CAROLINE BATTISTI 1 ELISETE PEREIRA DE SOUZA 1,2 PEDRO BINS ELY 1,2 35ª Jornada Sul Brasileira de Cirurgia Plástica…”
Section: Objetivounclassified
“…O carcinoma de células escamosas é a neoplasia maligna mais frequente dos lábios, localizando-se no lábio inferior, em cerca de 90% dos casos, em virtude da maior exposição cumulativa à radiação ultravioleta, o principal fator etiopatogênico 1,2 . Outros possíveis fatores favorecedores são os hábitos de tabagismo e álcool, a imunossupressão e a infecção crônica pelo papilomavírus humano.…”
Section: Introductionunclassified
“…Furthermore, the mast cell population was higher in squamous cell carcinoma of the lip than oral mucosal epithelium. Another study showed that the increase in mast cell population was unrelated to the degree of differentiation of the tumour [56]. One study showed serum elevation of mast cell tryptase in patients with oral squamous cell carcinoma, but it was not correlated with the staging of cancer (i.e.…”
Section: Evidence-based Report On the Role Of Mast Cells In Oral Squamentioning
confidence: 99%
“…É citado na literatura um possível papel dos MCs em síntese aumentada de colágeno e de fibrose na pele induzida por radioterapia. (1,22,23,24) Roberts e Brenchley (15) O processo fibrótico pesquisado em rins é caracterizado por um infiltrado inflamatório crônico e pela proliferação de miofibroblastos no interstício. Este processo é conduzido por uma rede de citocinas que inclui fatores de crescimento para miofibroblastos, tais como PDGF, bFGF.…”
Section: Participação De Mastócitos Na Fibroseunclassified